Acid rock drainage and metal leaching from mine waste material (tailings) of a Pb-Zn-Ag skarn deposit: environmental assessment through static and kinetic laboratory tests - Blanca Adriana Méndez-Ortiz; Alejandro Carrillo-Chávez; Marcos Gustavo Monroy-Fernández (Revista Mexicana de Ciencias Geológicas)
In this work, the processes and products involved in the generation of acid rock drainage – metal leaching (ARD-ML) from mine waste material (tailings) derived from the exploitation of an ore type Pb- Zn-Ag skarn were characterized. Laboratory tests (static and kinetic) of historic and recent tailings were conducted along with the mineralogical characterization of solids, and chemical analyses of solids and leachates. Pyrite (FeS2) is the most abundant sulfide phase, and one of the main minerals promoting ARD- ML generation, followed by pyrrhotite (Fe1-xS) and arsenopyrite (FeAsS). Carbonates are present as calcite (CaCO3) and lesser amounts of ankerite [Ca(Fe,Mg)(CO3)2]. Also, smaller concentrations of quartz and feldspar were identified. Results of the static tests (acid base accounting: ABA) indicate that both, recent and historic tailings, have a likely ARD-ML potential (neutralization potential, NP <1). Kinetic tests were performed in humidity cells to simulate the natural oxidation of primary mineral samples; the obtained leachates had circum-neutral pH values (4.5–7.9) and relatively low heavy metals contents. Nevertheless, oxidation-neutralization curves suggest that oxidation capacity in both sample types is higher than their neutralizing capacity, and that sulfide oxidation is more important in historic than in recent tailings. The obtained information, along with statistical tests (F ratio and t-student), demonstrated that the tailings have a strong capacity to generate ARD-ML, and that the particular characteristics of the historic and recent mine waste materials created different conditions for the generation of ARD-ML.